Skeletal Muscle Microvascular Changes in Response to Short-Term Blood Flow Restricted Training—Exercise-Induced Adaptations and Signs of Perivascular Stress - Nielsen, Jakob L.; Frandsen, Ulrik; Jensen, Kasper Y.; Prokhorova, Tatyana A.; Dalgaard, Line B.; Bech, Rune D.; Nygaard, Tobias; Suetta, Charlotte; Aagaard, Per (Frontiers in Physiology, 2020)
Aim: Previous reports suggest that low-load muscle exercise performed under blood-flow restriction (BFR) may lead to endurance adaptations. However, only few and conflicting results exist on the magnitude and timing of microvascular adaptations, overall indicating a lack of angiogenesis with BFR training. The present study, therefore, aimed to examine the effect of short-term high-frequent BFR training on human skeletal muscle vascularization. Methods: Participants completed 3-weeks of high-frequent (1-2 daily sessions) training consisting of either BFR exercise (n=10, 22.8±2.3 years; 20%-1RM, 100-mmHg) performed to concentric failure (BFRE) or work-matched free-flow exercise (N=8, 21.9±3.0 years; 20%-1RM) (CON). Muscle biopsies (VL) were obtained at baseline, 8 days into the intervention, and 3 and 10 days after cessation of the intervention to examine capillary and perivascular adaptations, as well as angiogenesis-related protein signalling and gene expression. Results: Capillary per myofiber and capillary area increased 21-24% and 25-34%, respectively in response to BFRE (P<0.05-0.01), while capillary density remained unchanged. Overall, these adaptations lead to a consistent elevation (15-16%) in the capillary-to-muscle area ratio following BFRE (P<0.05-0.01). In addition, evaluation of perivascular properties indicated thickening of the perivascular basal membrane following BFRE. No or only minor changes were observed in CON. Conclusions: This study is the first to show that short-term high-frequent, low-load BFRE can lead to microvascular adaptations (i.e. capillary neoformation and changes in morphology), which may contribute to the endurance effects previously documented with BFR training. The observation of perivascular membrane thickening suggests that high-frequent BFRE may be associated with significant vascular stress.